Perspective of Patient Advocacy Groups on Clinical Research and Outcomes of Their Involvement - Poonam Bagai; Pooja Sharma; Aala Ansari; Nirbhay Singh; Rhea Aggarwal; Durga Chougule; Sonal Sharma; Padam Singh; Manish Kumar Singh; Gargi Singh; Sanjeev Singh (Journal of Clinical and Preventive Cardiology)
Background: Patient advocacy groups (PAGs) play a crucial role in connecting patients, researchers, clinicians, and clinical research. Equipping PAGs with the knowledge to raise awareness about clinical research through targeted educational programs will ultimately enhance their impact. In this questionnaire-based study, the knowledge, awareness, and perspectives on clinical research among PAGs as well as the outcome of their involvement in awareness program were explored. Methods: Unbox research was a cross-sectional questionnaire-based survey of 22 questions evaluating the knowledge, awareness, and perspectives of participants enrolled in Patient Advocates for Clinical Research (PACER) awareness program. The survey was followed by a FGD to explore the experiences of the participants with the PACER program. Results: Among 185 participants, 97.8% were aware about clinical research/trials and 90.3% understood clinical trials are conducted before any drug reaches market. Participants identified safety concerns (82.2%), limited knowledge (67.6%), and fear (58.9%) as key reasons for barriers for participation. Participants prioritized increased patient participation (59.5%), availability of more clinical trials (54.6%), and substantial investment in healthcare (51.9%) as key drivers for developing India’s healthcare system. About 88.6% of participants believed that involvement of PAGs in clinical trials will benefit the patients. The FGD revealed a significant progress by PAGs. The active involvement of PAGs led to their inclusion on ethics committees and helped enroll 14 patients in clinical trials within just six months. Conclusion: The study underscores the positive impact of programs like PACER in powering PAGs and other stakeholders. Increased knowledge, awareness, and collaboration led to significant outcomes for patients, clinicians, and researchers.